Manifestasi Circular Economy dan Environmental Accounting pada Bank Sampah Induk Surabaya sebagai Khalifah fil Ard - Selvia Eka Aristantia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The role of waste banks is very large in encouraging the development of a circular economy and its implementation. Waste banks have a vital role in supporting circular economy efforts. Even though the circular economy concept is not new, scientific literature or research regarding the circular economy leading to Waste Banks is still limited. This research aims to determine the manifestation of the Surabaya main waste bank in the Circular Economy and Environmental Accounting movement as Khalifah fil Ard using a case studies approach. The result is that the Circular Economy manifestation at the Surabaya main waste bank has been carried out well by fulfilling the 6R principles. Researchers can detect environmental accounting at the Surabaya Main Waste Bank in the recycling income account and the various costs incurred are generally categorized as prevention costs.